Acoustic Analysis Before and After Voice Therapy for Laryngeal Pathology - Chhetri, S.S.; Gautam, R. (Kathmandu University Medical Journal, 2017)
Background Voice problems caused by pathologies in vocal folds are well known. Some types of laryngeal pathologies have certain acoustic characteristics. Objective evaluation helps characterize the voice and voice problems providing supporting evidences, severity of disorders. It helps assess the response to the treatment and measures the outcomes. Objective The objective of the study is to determine the effectiveness of the voice therapy and quantify the results objectively by voice parameters. Method Study includes 61 patients who presented with different types of laryngeal pathologies. Acoustic analyses and voice assessment was done with Dr. Speech ver 4 (Tiger DRS Inc.). Acoustic parameters including fundamental frequency, jitters, shimmers, Harmonic to noise ratio (HNR), Normalized noise energy (NNE) were analyzed before and after voice therapy. Result Bilateral vocal nodules were the most common pathologies comprising 44.26%. All acoustic parameters showed a significant difference after the therapy (p<0.05) except for NNE. Dysphonia due to vocal fold polyp showed no improvement even after voice therapy (p>0.05). Conclusion Acoustic analysis provides an objective, recordable data regarding the voice parameters and its pathologies. Though, few pathology require alternative therapy rather than voice therapy, overall it has a good effect on glottic closure. As the voice therapy can improve the different indices of voice, it can be viewed as imperative part of treatment and to monitor progression.